(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
The decision of the Swiss National Bank of giving up the fixed rate of 1,2 Euro/CHF on the 15th of January 2015, a rate established at its admission to the Monetary Economic Union, had consequences on Central and Eastern European countries because a great part of the credits granted were in Swiss francs. In all these countries, the national currencies depreciated and the financial market rates were reduced. Regional banks started to face difficulties regarding the management of the situation and were under the necessity of finding solutions to avoid the risk of not recovering the granted credits. The issue of the Swiss franc appreciation was treated differently by the analysed countries and took into consideration the particularities characteristic to the credits granted in this currency. The present paper aims at emphasising the impact of the Swiss franc appreciation on the Romanian banking system but also the approach of other countries in Central and Eastern Europe in this respect.